Predictors of the Frequency of Consumption and Purchase of Convenience Food in Modelling Approaches - Platta , Anna; Mikulec , Anna; Mikulec, Karolina; Radzymińska, Monika; Suwała, Grzegorz (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2025)
Objective: To determine the variables influencing the frequency of consumption and purchase of convenience foods with the use of economic modelling. Research Design & Methods: The empirical material consisted of the results obtained using computer-assisted web interviewing methodology (by means of Google Forms). The study was conducted among 393 respondents living in Gdynia (Northern Poland). The survey included questions in the following areas: lifestyle, attitudes towards new products, selection attributes of convenience foods, frequency of consumption and purchase of convenience foods, as well as demographic data (gender, age, and income). To achieve the objectives of the study, logistic regression analysis was used, thus predicting the probability of a set of independent variables influencing the regularity of purchasing convenience foods and the frequency of purchasing convenience food products for direct consumption (ready-to-eat). Findings: Men were found to be almost three times more likely to consume convenience foods on a regular basis as women. In turn, individuals belonging to Generation Y have an approximately 70% higher chance of consuming convenience food products more regularly than representatives of Generation X. Moreover, the subjects for whom the freshness of consumed food is very important are about 59% less likely to purchase products for direct consumption (ready-to-eat) than individuals for whom the freshness of consumed products is not so important. Implications / Recommendations: A potential segment of convenience food consumers are men, individuals from Generation Z, who value both the freshness and short preparation time of the products. Therefore, building awareness of convenience food brands/products should be especially targeted at this group of buyers. Contribution: The presented models expand the knowledge of the factors determining the consumption of convenience foods.